The COVID-19 Pandemic and the State of Emergency: Lessons from Portugal - Violante, Teresa (Democracy after Covid. Challenges in Europe and Beyond, 2022)
The present chapter analyses the normative response of Portugal to the coronavirus crisis. As in other European Member States, the reaction to the pandemic was developed through a combination of enactment of the constitutional state of emergency with the statutory administrative emergency regime. Under both frameworks, there has been a strengthening of the executive at the expense of a parliamentary retreat. This chapter covers both responses to the pandemic and their shortcomings, mainly regarding the lack of democratic legitimation of the fight against the pandemic in face of a parliamentary circumvention and abdication.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Administrative emergency; Constitutional emergency; Constitutional exception; Fundamental rights’ restrictions; Separation of powers; State of emergency